PROGRAM SIWAB UNTUK MENINGKATKAN POPULASI SAPI POTONG DAN NILAI EKONOMI USAHA TERNAK (Forum Penelitian Agro Ekonomi, 2024)
Siwab or its extension Mandatory cattle breeding is a manifestation of government commitment in increasing beef cattle population, and as a target for meat sufficiency in 2026. The program is believed to lead Indonesia to achieve beef self-sufficiency in the next 5-10 years. Beef cattle can be maximized in order to produce calves, and become a government’s focused program on enhancing beef cattle production through artificial insemination (AI). Based on the above problems, the government hopes to develop the program, it should not fail the umpteenth time to fulfil meat needs of the country. The purpose of this review is to describe the SIWAB program and the economic value of female beef cattle produced by AI which produces calf. This study approach is done through literature reviews related to SIWAB program implementation. SIWAB program includes two main programs namely the increase of porong cattle population through artificial insemination of AI and natural mating (Inka). With the AI through prgram, the parent beef cattle can regulate the cow's birth well. The mother cow bunting AI results can increase the selling value higher and can improve the welfare of farmers. The government's policy to pursue targeted beef self-sufficiency by the year 2026 is achieved, but the program must be responded and done well. Government policy to boost short-term beef cattle population can help to meet the needs of beef consumption, and in the long run the economic impact of farmers.
Keywords: SIWAB; improving; population; economic value; farmers